2016
DOI: 10.1016/j.redox.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol inhibits hydrogen peroxide-induced apoptotic signaling via labile iron chelation

Abstract: Although it is known that Mediterranean diet plays an important role in maintaining human health, the underlying molecular mechanisms remain largely unknown. The aim of this investigation was to elucidate the potential role of ortho-dihydroxy group containing natural compounds in H2O2-induced DNA damage and apoptosis. For this purpose, the main phenolic alcohols of olive oil, namely hydroxytyrosol and tyrosol, were examined for their ability to protect cultured cells under conditions of oxidative stress. A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 40 publications
4
53
0
3
Order By: Relevance
“…These data hint at the possible links between Yap and mitochondria. Recent research has found that Yap preserves mitochondrial function via regulation of JNK pathways ( 54 ). In the present study, we confirmed that the protective effect of Yap on mitochondria was attributed to mitophagy activation.…”
Section: Discussionmentioning
confidence: 99%
“…These data hint at the possible links between Yap and mitochondria. Recent research has found that Yap preserves mitochondrial function via regulation of JNK pathways ( 54 ). In the present study, we confirmed that the protective effect of Yap on mitochondria was attributed to mitophagy activation.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from cells using TRIzol™ reagent (Invitrogen; Thermo Fisher Scientific, Inc.). A total of 1 µg RNA from each sample was reverse-transcribed into cDNA using an RT kit (Eurogentec, Liege, Belgium) ( 36 ). The qPCR was performed with primers and matched probes from the Universal Fluorescence-labeled Probe Library (Roche Diagnostics GmbH).…”
Section: Methodsmentioning
confidence: 99%
“…JNK has been reported as the stress-activated protein kinases in the liver [60] , and activation of JNK induces inflammation and apoptosis [61] . JNK has a close relationship with c-Jun, a kind of phosphorylation activated transcription factor.…”
Section: Discussionmentioning
confidence: 99%